A Yogācāra Buddhist theory of metaphor - Tzohar, Roy (Oxford University Press, 2018)
The Yogācāra school of Buddhist thought claims that all language use is metaphorical. Exploring the profound implications of this assertion, Roy Tzhoar makes the case for viewing the Yogacara account as a full-fledged theory of meaning, one that is not merely linguistic, but also applicable both in the world and in texts